Efficacy and safety of Mazdutide on weight loss among diabetic and non-diabetic patients: a systematic review and meta-analysis of randomized controlled trials - Nalisa, David Lubasi; Cuboia, Nelson; Dyab, Eman; Jackson, Idongesit Linus; Felix, Habimana Jean; Shoki, Pantaleon; Mubiana, Mary; Oyedeji-Amusa, Mariam; Azevedo, Luís; Jiang, Hongwei (Frontiers in Endocrinology, 2024)
Background: Overweight and obesity are increasing global public health problems. Mazdutide is a new dual agonist drug that can potentially reduce weight and blood glucose levels simultaneously. However, the synthesis of evidence on the efficacy and safety of this drug is scarce. Therefore, this study aimed to synthesize evidence on the efficacy and safety of Mazdutide compared to placebo on weight reduction among adults with and without diabetes.We conducted a systematic review and meta-analysis of randomized controlled trials (RCTs). Data were retrieved from six electronic databases: PubMed, Web of Science, Scopus, Cochrane Library, ClinicalTrial.gov, and Google Scholar, and manually searched from the included references. The data were synthesized using a random effect model. This analysis was performed in the R programming language using the Meta package.Results: A total of seven RCTs involving 680 participants were included in this study.Mazdutide was more effective in reducing body weight (mean difference [MD]= -6.22%, 95% confidence interval [CI]: -8.02% to -4.41%, I 2 = 90.0%), systolic blood pressure (MD = -7.57 mmHg, 95% CI: -11.17 to -3.98 mmHg, I 2 =46%), diastolic blood pressure (MD = -2.98 mmHg, 95% CI: -5.74 to -0.22 mmHg, I 2 =56%), total cholesterol (MD = -16.82%, 95% CI -24.52 to -9.13%, I 2 = 61%), triglycerides (MD = -43.29%, 95%CI -61.57 to -25.01%, I 2 = 68%), low-density lipoprotein (MD= -17.07% , 95% CI -25.54 to -8.60% , I 2 =53%), and highdensity lipoprotein (MD = -7.54%, 95% CI: -11.26 to -3.83%, I 2 = 0%) than placebo.Mazdutide was associated with reduced hemoglobin A1c (HbA1c) and fasting plasma glucose in participants with type 2 diabetes. In the subgroup and meta-regression analyses, weight reduction was more significant in non-diabetics compared to diabetics, and in those who received a longer treatment duration (24 weeks) than in those on shorter durations (12-20 weeks). Participants who received Mazdutide had a higher risk of mild or moderate gastrointestinal side effects.Mazdutite appears to be effective in weight reduction among patients with and without diabetes, and it has an advantage over other associated comorbidities. However, it was associated with mild or moderate gastrointestinal side effects.